Third-country exchange rate volatility and Japanese–US trade: evidence from industry-level data. Issue 16 (2nd April 2016) - Bahmani-Oskooee, Mohsen; Hegerty, Scott W.; Xi, Dan
ABSTRACT: As an important economic power globally as well as within Asia, Japan is susceptible to fluctuations in the yen versus both the dollar and its neighbours' currencies. The resulting risk, from both sources, might, therefore, have important effects on Japanese trade. This study incorporates third-country exchange rate volatility (both yen-renminbi and dollar-renminbi) into a reduced form trade model for industry trade between the US and Japan. As was the case with a previous study that did not include these effects, our cointegration analysis finds that most industries are unaffected by risk. Third-country effects are, however, significant in a number of cases. Interestingly, a large share of US industries find that exports increase due to third-country risk, suggesting that this volatility is encouraging traders to reorient their trade markets by substitution.